Effect of Avocades to LDL Cholesterol as a Preventive Risk of Atherosclerosis - Dr. dr. Shahrul Rahman, Sp.PD., Finasim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Cardiovascular disease is the highest cause of death in most developing countries. Hypercholesterolemia, especially high LDL is a risk factor for cardiovascular disease can be overcome through a good diet. Avocados are rich in fat. Avocado fat is included in healthy fats, because it is dominated by monounsaturated fatty acids oleate. Based on the description, it is necessary to do research on the effect of 1D>cado juice on fat profiles in humans